Solvability of quasilinear elliptic equations in large dimensions - Oleg Zubelevich (Electronic Journal of Differential Equations, 2005)
We study the solvability of quasilinear elliptic Dirchlet boundary-value problems. In particular, we show that if the dimension of the domain is large enough then the solution exists independent of the growth rate on right-hand side.